2020
DOI: 10.1097/yic.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of lithium clearance in patients with bipolar disorder

Abstract: Lithium is an effective agent approved for the treatment of bipolar disorder. It has narrow therapeutic window and significant variability in its pharmacokinetic. The aim of this study is to determine the population pharmacokinetics of lithium in patients with bipolar disorder in Saudi Arabia and to identify the factors that explain variability. A retrospective chart review was performed on patients with bipolar disorder who received oral lithium. The population pharmacokinetic models were developed using Mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Lithium is freely filtered through the glomeruli, and protein binding of lithium in the plasma is negligible. In our study, when patients had severe renal insufficiency (CRCL = 30 ml/min), the typical CL/F of lithium decreased by 23%, which was consistent with the results of the Alqahtani group ( Alqahtani et al, 2020 ). Their study in patients with bipolar disorder in Saudi Arabia suggested that the 15% lowering of CL, was attributed to the reduced renal clearance from 120 to 30 ml/min.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lithium is freely filtered through the glomeruli, and protein binding of lithium in the plasma is negligible. In our study, when patients had severe renal insufficiency (CRCL = 30 ml/min), the typical CL/F of lithium decreased by 23%, which was consistent with the results of the Alqahtani group ( Alqahtani et al, 2020 ). Their study in patients with bipolar disorder in Saudi Arabia suggested that the 15% lowering of CL, was attributed to the reduced renal clearance from 120 to 30 ml/min.…”
Section: Discussionsupporting
confidence: 91%
“…And the impact of CRCL and WT on the PK of lithium has been previously reported ( Jermain et al, 1991 ; ElDesoky et al, 2008 ; Perez-Castello et al, 2016 ; Alqahtani et al, 2020 ). This is an expected result, as lithium is mainly cleared via the kidney.…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, the mean serum aldosterone in both study groups was within normal physiological limits, and there were no significant differences. The change in serum aldosterone level over 12 weeks was not significant in both the groups and supports the findings of Pedersen et al 24 The correlation analysis was performed between baseline serum lithium and baseline serum aldosterone, and a positive correlation between the two variables was shown, which supports the findings of Pedersen et al and Stewart et al 24,27 Alqahtani et al and ElDesoky et al developed population pharmacokinetic models and found that creatinine clearance is the most significant covariate for lithium clearance 28,29 . Therefore, serum creatinine and creatinine clearance were two important parameters studied in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Lithium, the first-line drug treatment for BD, both for bipolar depression [256][257][258][259][260][261] and for mixed episodes [262][263][264][265][266][267][268][269][270][271][272][273][274] has numerous neuroprotective, neurotrophic, and neuroplastic effects [275][276][277][278]. In addition to being the mood stabilizer conventionally used in ameliorating the pathophysiology of BD, lithium has some antidepressant activity [279][280][281][282]. The therapeutic effects of lithium have been hypothesized to be partially linked to its antioxidant capabilities.…”
Section: Lithium Therapymentioning
confidence: 99%